2016
DOI: 10.1007/s00464-016-4851-8
|View full text |Cite
|
Sign up to set email alerts
|

Gaze entropy reflects surgical task load

Abstract: Our data show that gaze metrics are a valid and reliable surgical task load index. These findings have potential impacts to improve patient safety by providing accurate measurements of surgeon task (over-)load and might provide future indices to assess residents' learning curves, independently of expensive virtual simulators or time-consuming expert evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…Increases in both gaze transition entropy and hip displacement entropy indicate movements are becoming more complicated (or less predictable) and which has been previously associated with increases in functional task difficulty. 22,27 We hypothesized a non-linear relationship between fingertip strength and visuo-motor complexity such that during preview and climbing, complexity of visual search and hip movement would increase close to action boundaries (ie, when the required fingertip strength approaches the maximal fingertip strength) and decrease when far to action boundaries (ie, when the required fingertip strength was inside or outside the maximal fingertip strength).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in both gaze transition entropy and hip displacement entropy indicate movements are becoming more complicated (or less predictable) and which has been previously associated with increases in functional task difficulty. 22,27 We hypothesized a non-linear relationship between fingertip strength and visuo-motor complexity such that during preview and climbing, complexity of visual search and hip movement would increase close to action boundaries (ie, when the required fingertip strength approaches the maximal fingertip strength) and decrease when far to action boundaries (ie, when the required fingertip strength was inside or outside the maximal fingertip strength).…”
mentioning
confidence: 99%
“…21,37 Because some degree of change in how actions are organized for task success, a hallmark feature of behavior around these regions is the tendency for the individual to increase their movement variability. 22,38,39 Hence, future research might consider how visuo-motor complexity can be used as an indicator of learning potential for the design of perceptual-motor tasks (such as in 27 ). Another issue is to establish in what ways functional strength supports a greater variety of actions, including in adapting to more complex or difficult movement problems.…”
mentioning
confidence: 99%
“…Based on such concept, stationary gaze entropy ( H s ) is a method in which Shannon’s entropy equation ( 1 ) is applied to the probability distribution of fixation coordinates to calculate the average level of uncertainty in the spatial distribution of a sequence of fixations generated in a given timeframe 31 . Higher entropy or uncertainty, in this case, indicates a wider distribution of fixations across the visual field, suggesting greater dispersion of gaze 29 .…”
Section: Introductionmentioning
confidence: 86%
“…Gaze entropy (measured in bits ) refers to quantitative approaches that have been used to assess visual scanning behaviour during engagement in tasks with high visuospatial demand such as driving 25 , simulated aviation 26 – 28 and surgical procedures 29 . The concept of entropy used in these methods is that of information theory, which describes the amount of required information to generate a given sequence as a measure of overall uncertainty 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Krejtz et al calculated the transition entropy and stationary entropy when participants observed paintings from three classical periods and found that individuals’ visual attention switching behavior was related to their personal traits, interests, and recognition of stylized artwork [ 22 ]. Gaze entropy can also be used as a reliable surgical task load index, and increasing gaze entropy represents increased task complexity [ 23 , 24 ]. In the transportation domain, gaze entropy is also widely used to evaluate visual exploration features.…”
Section: Introductionmentioning
confidence: 99%